2009
DOI: 10.1016/s0377-1237(09)80133-0
|View full text |Cite
|
Sign up to set email alerts
|

Sedation Guidelines for Gastro Intestinal Endoscopy

Abstract: Effective sedation is usually a vital precursor to any successful endoscopic procedure. With advanced techniques and medications available today this component of the procedure can be dealt with safely and in an efficient manner. MJAFI 2009; 65 : 161-165

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Sedation was commonly used during endoscopy procedures because it can improve patient acceptance and tolerance via relieving discomfort and facilitating sympathetic patient management [1] . Lines of evidence demonstrated that sedation using optimal sedation and analgesia by endoscopist with or without help of anesthesiologist is safe and cost-efficient [1] – [3] . But cardiopulmonary adverse events (CAEs) that are related to conscious sedation occurred frequently during the procedures [1] , [4] [9] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedation was commonly used during endoscopy procedures because it can improve patient acceptance and tolerance via relieving discomfort and facilitating sympathetic patient management [1] . Lines of evidence demonstrated that sedation using optimal sedation and analgesia by endoscopist with or without help of anesthesiologist is safe and cost-efficient [1] – [3] . But cardiopulmonary adverse events (CAEs) that are related to conscious sedation occurred frequently during the procedures [1] , [4] [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Lines of evidence demonstrated that sedation using optimal sedation and analgesia by endoscopist with or without help of anesthesiologist is safe and cost-efficient [1] – [3] . But cardiopulmonary adverse events (CAEs) that are related to conscious sedation occurred frequently during the procedures [1] , [4] [9] .…”
Section: Introductionmentioning
confidence: 99%